Etiological Risk Factors for Men Becoming Sexual Perpetrators Who Prey on Underage Victims. Issue 1 (2nd April 2020) - Stroebel, Sandra S.; O'Keefe, Stephen L.; Griffee, Karen; Harper-Dorton, Karen V.; Beard, Keith W.; Young, Debra H.; Swindell, Sam; Steele, Kerri; Stroupe, Walter E.; Kuo, Shih-Ya; Hershman, Cassandra M.
Abstract: Risk factors for men becoming sexual perpetrators against underage victims were identified using data provided by 1, 556 respondents who had been guaranteed unbreakable anonymity. Early behaviors occurring while the respondents and their partners were both under the age of 18 increased the risk that the respondents would begin masturbating using images of the same sex as their early partners. Masturbating using images of underage children and early experiences with children and adolescents increased the likelihood that the respondents would become adults who preyed on partners who were of an age and sex similar to those early underage partners and images.